Long-term internal erosion mechanism of organic matter in sediments solidified by cement, lime, and metakaolin - Wang, Hongxing; Zhang, Dizhi; Wu, Shangwei; Jing, Xiaofei; Liu, Kehui; Ren, Lingyan (Frontiers in Earth Science, 2023)
In applications of stabilized/solidified (S/S) sediments, the organic matter inside the original sediments will decompose and release fulvic acid (FA) and humic acid (HA) gradually, which may reduce the durability of the S/S sediments. It is critical to understand the long-term internal erosion mechanism to improve the durability of S/S sediments. Thus, S/S sediments solidified by commonly used cement, lime, and metakaolin were first prepared in the laboratory. Reasonable proportioning of the additives was determined through orthogonal tests. Unconfined compression strength tests, measurements of organic environment indexes and chemical environment indexes, and scanning electron microscopy analysis were then conducted after different curing periods of the S/S sediments to explore the erosion mechanism. The following results and conclusions were obtained. 1) The microstructure of S/S sediments is composed of a sediment aggregate core, a hydrated calcium silicate (CSH) shell covering the core, and calcium hydroxide (CH) submerged in the CSH shell. 2) HA and FA are released gradually by organic matter decomposition inside the core and are consumed by neutralization reactions with solidification products. 3) The dissipation process of organic matter and the induced damage process of S/S sediments can be partitioned into three stages: in the first stage, HA and FA jointly neutralize the solidification products inside the CSH shell, the CSH shell is eroded gradually, and the S/S sediments lose strength gradually; in the second stage, the neutralization reactions are still inside the CSH shell, but only occur between FA (not HA) and the solidification products, the CSH shell breaks down at the end of this stage, but the S/S sediments do not lose much strength until the end point; and in the third stage, neutralization reactions take place outside the CSH shell between HA (but not FA) and the solidification products, and the S/S sediments lose strength dramatically. It was also concluded that HA (rather than FA) is more likely to neutralize solidification products in a more alkaline environment; HA has much stronger chemical affinity with Ca2+ ions than FA; HA controls the strength loss of S/S sediments, whereas FA controls the working status of HA; and the developments of HA content and Ca2+ ion concentration reflect the strength loss of S/S sediments.